Orthogonal Latin Squares and Incomplete Balanced Block Designs - Bedrosian, Peter (My University, 1953)
Methods of constructing orthogonal Latin of squares and incomplete balanced block designs are developed. The analysis of these designs is then derived. Particular care is taken in the determination of the number of degrees of freedom involved, a point which is usually neglected in other sources. The principle source of material for this thesis has been H.B. Mann's book, Analysis and Design of Experiments.
Keywords: orthogonal Latin squares; designs